" . . . A Bit of a Joke": Policy and Workplace Bullying. (June 2020) - Hodgins, Margaret; Lewis, Duncan; MacCurtain, Sarah; McNamara, Patricia; Hogan, Victoria; Pursell, Lisa
Workplace bullying is pervasive and has negative impacts on organizations and their employees. Despite this, organizations generally do not deal well with the problem. Anti-bullying, or Dignity-at-Work policies, do not adequately protect employees from the harms caused by bullying. This study, based on data from the 2018 Irish Workplace Behavior Study, explores experience of organizational responses to workplace bullying, drawing on interviews with participants from three large Irish organizations. One overarching theme and five sub themes emerged from the thematic content analysis, reinforcing earlier findings regarding the complex and problematic nature of workplace bullying and opaque "ownership" of anti-bullying or Dignity-at-Work policy and its implementation. The study concludes that organizations must actively establish a culture of interpersonal respect, rather than simply instituting a policy where ultimately no one takes responsibility. Facilitating employee wellbeing requires social cohesion across an organization.